Three-dimensional rotational angiography of the left atrium and the oesophagus: the short-term mobility of the oesophagus and the stability of the fused three-dimensional model of the left atrium and the oesophagus during catheter ablation for atrial fibrillation - Starek, Zdenek; Lehar, Frantisek; Jez, Jiri; Scurek, Martin; Wolf, Jiri; Kulik, Tomas; Zbankova, Alena; Novak, Miroslav (Europace, 2017)
AIMS: The objective of this study was to evaluate the mobility of the oesophagus and the stability of the three-dimensional (3D) model of the oesophagus using 3D rotational angiography (3DRA) of the left atrium (LA) and the oesophagus, fused with live fluoroscopy during catheter ablation for atrial fibrillation. METHODS AND RESULTS: From March 2015 to September 2015, 3DRA of the LA and the oesophagus was performed in 33 patients before catheter ablation for atrial fibrillation. Control contrast oesophagography was performed every 30 min. The positions of the oesophagograms and the 3D model of the LA and the oesophagus were repeatedly measured and compared with the spine. The average shift of the oesophagus ranged from 2.7 ± 2.2 to 5.0 ± 3.5 mm. The average real-time oesophageal shift ranged from 2.7 ± 2.2 to 3.8 ± 3.4 mm. No significant shift was detected until the 90th minute of the procedure. The average shift of the 3D model of the LA and the oesophagus ranged from 1.4 ± 1.8 to 3.3 ± 3.0 mm (right-left direction) and from 0.9 ± 1.2 to 2.2 ± 1.3 mm (craniocaudal direction). During the 2 h procedure, there were no significant shifts of the model. CONCLUSION: During catheter ablation for atrial fibrillation, there is no significant change in the position of the oesophagus until the 90th minute of the procedure and no significant shift in the 3D model of the LA and the oesophagus. The 3D model of the oesophagus reliably depicts the position of the oesophagus during the entire procedure.
Keywords: Imaging, Three-Dimensional; Anatomic Landmarks; Esophagus; délka operace; anatomická značka; Mobility of the oesophagus; Motion; Humans; lidé středního věku; Predictive Value of Tests; chirurgie s pomocí počítače; fluoroskopie; Female; Aged; 3D Rotational angiography of the left atrium and oesophagus; angiografie; výsledek terapie; senioři; lidé; Atrial Fibrillation; Radiography, Interventional; Heart Atria; katetrizační ablace; Catheter ablation of atrial fibrillation; reprodukovatelnost výsledků; časové faktory; pohyb těles; Fluoroscopy; Operative Time; Angiography; ženské pohlaví; Surgery, Computer-Assisted; Male; Reproducibility of Results; Middle Aged; prediktivní hodnota testů; Atrioesophageal fistula; Treatment Outcome; ezofágus; Radiographic Image Interpretation, Computer-Assisted; srdeční síně; zobrazování trojrozměrné; rentgenový obraz - interpretace počítačová; Image integration; intervenční radiografie; mužské pohlaví; prospektivní studie; Catheter Ablation; Time Factors; fibrilace síní; Prospective Studies